2020
DOI: 10.1111/jan.14440
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing postpartum blood glucose screening among women with prior gestational diabetes mellitus in a rural community

Abstract: Aims:The aims of the present study were: a) to investigate the current state of postpartum glucose screening in rural China; and b) to explore the factors influencing postpartum blood glucose screening among women with prior GDM based on Andersen's behavioural model of health service use. Design:A multisite, cross-sectional study design, conducted from November 2017 to January 2018.Methods: A total of 465 women with prior GDM were included from two countylevel hospitals in rural China. The potential influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…This index is similar to that found by Ortiz et al, 15 who found a rate of 19%. The prevalence of DM screening in patients with a history of GDM is quite variable in the literature, ranging from 13.8% to 41%, but what all the studies 13,14,[16][17][18][19] show, including the current study, is that even though screening is indicated for all postpartum women with a history of GDM, its performance is still low. Screening is important, as it enables the establishment of the risks of developing DM, so physicians can prescribe behavioral or even pharmacological changes to prevent or delay the its diagnosis in this population and avoid the impacts of this comorbidity in the long term.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This index is similar to that found by Ortiz et al, 15 who found a rate of 19%. The prevalence of DM screening in patients with a history of GDM is quite variable in the literature, ranging from 13.8% to 41%, but what all the studies 13,14,[16][17][18][19] show, including the current study, is that even though screening is indicated for all postpartum women with a history of GDM, its performance is still low. Screening is important, as it enables the establishment of the risks of developing DM, so physicians can prescribe behavioral or even pharmacological changes to prevent or delay the its diagnosis in this population and avoid the impacts of this comorbidity in the long term.…”
Section: Discussionmentioning
confidence: 60%
“…The sampling was carried out by convenience, with an estimated sample size of 175 cases. The calculation was performed with the OpenEpi software, version 3, considering the significant variables from previous studies, 13 14 with bilateral significance (1-α) of 0.05 and power (1-β) of 0.80, and an estimated loss of up to 30%.…”
Section: Methodsmentioning
confidence: 99%